Adsorption and separation of the C3 hydrocarbons on cationic FER zeolites: Effect of dual sites existence - Koudelková, Eva; Gherib, Yosra; De Oliveira Ramos, Francisca Solanea; Čičmanec, Pavel; Bulánek, Roman (Elsevier Science BV, 2019)
Adsorption and co-adsorption of propane and propene were investigated by combination of calorimetric-volumetric measurements with breakthrough experiments on alkali metal exchanged (Li, Na-, K-) FER zeolites with different Si/Al ratio. Effect of cation type and their concentration in the zeolite on adsorption selectivity was evaluated and discussed. Based on determined adsorption heats at zero coverage limit, the bridged complexes of propene were confirmed only in the case of K-FER zeolites. Presence of bridged complexes between two nearby K+ cations in dual cationic sites, described in details previously (Rubes et al. J. Phys. Chem. C 122 (2018) 6128), results in significant increase in adsorption selectivity while adsorption capacity of the zeolite is not influenced and is comparable with other M-FER zeolites. On the other hand, Na-FER zeolites exhibited the lowest propene/propane selectivity (at least six-times lower than K-FER-8.6 zeolite).
Adsorpce a separace C3 uhlovodíků na kationtových FER zeolitech: Efekt existence duálních poloh
Keywords: Zeolite; Bridged complexes; IAST selectivity; Propane; Propene; zeolit; můstkové komplexy; IAST selektivita; propan; propen